Analysis of disease progression and prognosis in differentiated thyroid cancer with pulmonary metastases: a retrospective study. Issue 5 (9th October 2020) - Iwasaki, Hiroyuki; Toda, Soji; Murayama, Daisuke; Matsui, Ai
Abstract : Introduction: Pulmonary metastasis originating from differentiated thyroid cancer is rare. Pulmonary metastasis generally progresses slowly and results in a relatively long prognosis when treated with radioactive iodine therapy and thyroid-stimulating hormone suppression therapy. However, some cases still result in death. Since 2015, lenvatinib administration for pulmonary metastases with disease progression has yielded satisfactory results. Materials and methods: Among the 798 patients with differentiated thyroid cancer treated at Kanagawa Cancer Center, Japan, between April 2015 and March 2020, 194 had distant metastasis. Of these 194 patients, 118 diagnosed with pulmonary metastasis had lesions that influence the prognosis. We retrospectively investigated the transition of the maximum diameter of pulmonary metastases, serum thyroglobulin, follow-up, and survival time. Results: We included 83 follow-up cases and 35 patients treated with lenvatinib. Considering that the disease progressed, 35 patients were treated with lenvatinib, and 4 died from cancer-specific disease. Treatment results were evaluated as progressive disease, stable disease, and partial response in 2, 11, and 22 patients, respectively. Conclusions: Among pulmonary metastases, no death occurred because of relatively slow disease progression up to a maximum diameter of 10 mm. However, when the size exceeded 15 mm, radioactive iodine treatment and thyroid-stimulating hormone suppression therapy did not work, and disease progression accelerated. As long as the lenvatinib treatment could be continued, the disease could be controlled satisfactorily. The patients who discontinued lenvatinib died from disease progression.